2015
DOI: 10.1158/1535-7163.mct-14-0928
|View full text |Cite
|
Sign up to set email alerts
|

MCL-1 Is a Key Determinant of Breast Cancer Cell Survival: Validation of MCL-1 Dependency Utilizing a Highly Selective Small Molecule Inhibitor

Abstract: Hyperexpression of antiapoptotic BCL-2 family proteins allows cells to survive despite the receipt of signals that would ordinarily induce their deletion, a facet frequently exploited by tumors. Tumors addicted to the BCL-2 family proteins for survival are now being targeted therapeutically. For example, navitoclax, a BCL-2/ BCL-X L /BCL-W inhibitor, is currently in phase I/II clinical trials in numerous malignancies. However, the related family member, MCL-1, limits the efficacy of navitoclax and other chemot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
118
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(130 citation statements)
references
References 46 publications
12
118
0
Order By: Relevance
“…In breast cancers, overexpression of MCL-1 is associated with a poor prognosis2, consistent with the dependency of breast cancer cells, including those of the TNBC subtype, on MCL-1 for survival349. Nonetheless, few insights have been available regarding the mechanisms responsible for MCL-1 overexpression in breast cancer.…”
Section: Discussionmentioning
confidence: 88%
“…In breast cancers, overexpression of MCL-1 is associated with a poor prognosis2, consistent with the dependency of breast cancer cells, including those of the TNBC subtype, on MCL-1 for survival349. Nonetheless, few insights have been available regarding the mechanisms responsible for MCL-1 overexpression in breast cancer.…”
Section: Discussionmentioning
confidence: 88%
“…The efficacy of the combination of ABT-263 and A-1210477 has been tested before in non-melanoma cancers 31,69 ; however, the mechanism of combination-induced cell death has not been analyzed. We utilized multiple approaches to investigate the contribution of NOXA and BIM, including the CRISPR/Cas9, shRNA techniques, as well as a NOXA-null line.…”
Section: Discussionmentioning
confidence: 99%
“…By inhibiting MCL-1, A-1210477 was shown to interact synergistically with the BCL-2/BCL-xL inhibitor ABT-263 (navitoclax) to kill a variety of cancer cell types (34)(35)(36). We found that the combination of A-1210477 and cobimetinib was synergistic as shown by a mechanism that involved disruption of the interaction of MCL-1 with the pro-apoptotic BH3-only proteins BIM and BAK by A-1210477, and by the ability of cobimetinib to suppress MCL-1 and induce BIM expression.…”
Section: Discussionmentioning
confidence: 99%